The Equilibrium Law For any general reaction system the value of Keq is called the equilibrium constant for the reaction. for example: 3 H2(g) + N2(g) <=====>  2 NH3(g) + heat Keq =      [NH3]2                                       [H2]3[N2] The above equation is called the Equilibrium Law Expression and it is a general form of the Law of Mass Action. Law of Mass Action In a system at equilibrium, at a fixed temperature, the product of the equilibrium concentration of the products divided by the product of the concentrations of the reactants, each being raised to the coefficient of the substance in the equation, must be equal to a constant. This law can only be applied to ideal gases and solution. (There are some reactions that do go all the way). Here is another example of an equilibrium law expression. H2(g) + I2(g) <=====>   2 HI(g) + heat Write equilibrium law expressions for each of the following reactions: a) 2 NO(g) + O2(g) <=====>   2 NO2(g) b) 2 SO2(g) + O2(g) <======>   2 SO3(g) c) SO2(g) + ½O2(g)  <======>  SO3(g) d) SO3(g) <======>   SO2(g) + ½O2(g) e) 4 HCl(g) + O2(g)  <======>  2 H2O(g) + 2 Cl2(g) Some of the equations above are almost carbon copies of each other except for the values of the coefficients. A couple of general rules should help. Keq(reverse) =          1                          Keq(forward) Any reaction written normally can have a Keq value. But does this Keq value stay the same if the reaction is flipped over and written in reverse. No, if the equation flips the Keq value becomes the inverse. At any given temperature there will be numerous [  ] values that will satisfy a constant Keq value.